Peningkatan Kapabilitas UMKM Kuliner Kota Malang melalui Pelatihan Keuangan Bisnis - Irma Kurniasari; Refiana Dwi Maghfiroh; Dimas Nugroho Dwi Seputro (Asthadarma : Jurnal Pengabdian Kepada Masyarakat, 2024)
The era of the Industrial Revolution 4.0 has transformed many aspects of life, including entrepreneurship. In this context, the development of SMEs (Small and Medium Enterprises) entrepreneurship has become a strategic issue crucial to supporting the vision of a Progressive Indonesia. This development is carried out through synergy in mapping entrepreneurial potential, creating a conducive business climate, fostering entrepreneurship, business incubation, and providing adequate financial support. According to data from the Central Statistics Agency (BPS) in 2023, SMEs in Indonesia contribute 61% to the GDP, absorbing around 117 million workers. However, one of the main challenges for SMEs is financial management that remains suboptimal. This study highlights the importance of effective financial management for business sustainability, especially for SMEs in Malang City that still face challenges in separating personal and business finances. The Community Service Program by the Faculty of Economics and Business at Universitas Pembangunan Nasional Veteran Jawa Timur focuses on financial literacy training for SMEs, emphasizing the importance of proper financial planning and management. This training aims to enhance SMEs' abilities in preparing simple financial statements and managing capital wisely, thereby supporting the growth and sustainability of culinary SMEs in Malang City.